Convalescent plasma therapy in severe coronavirus disease-2019: A narrative review - Rasmi Ranjan Sahoo; Kasturi Hazarika; Prashant Bafna; Manesh Manoj; Anupam Wakhlu (Indian Journal of Rheumatology)
Passive immunotherapy using whole blood or plasma from recovered patients is a potential therapeutic strategy for infections with no known drug therapy or prophylactic vaccines. Much before, the concept of transfusing neutralizing antibodies through convalescent blood or plasma was established; this modality demonstrated its effectiveness in containing the havoc caused by diphtheria and tetanus during the early 20th century. Convalescent blood products were effective in reducing the mortality risk when administered early in the disease course during the deadliest pandemic of Spanish flu in 1918. Even in the antibiotic era, the use of passive immunization strategy continued to expand with promising results against measles, Ebola, Argentine hemorrhagic fever, and Zika viruses. It was also effective in reducing the mortality and viral load in severe acute respiratory syndrome, H5N1, H1N1, and Middle East Respiratory Syndrome. Convalescent plasma administration carries the risk of anaphylactic reactions, transfusion-related acute lung injury, and transfusion-associated circulatory overload, but these are extremely rare. The impact of the recent coronavirus disease 2019 is enormous with significant morbidity and mortality. Until, a specific antiviral therapy or an effective vaccine is made available, the consideration for use of convalescent blood products, especially plasma, is warranted. Conceptual and observational wisdom often blossoms among therapeutic penury.